2012
DOI: 10.1007/s10529-012-1012-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant β-1,3-glucanases: their biological functions and transgenic expression against phytopathogenic fungi

Abstract: β-1,3-Glucanases are abundant in plants and have been characterized from a wide range of species. They play key roles in cell division, trafficking of materials through plasmodesmata, in withstanding abiotic stresses and are involved in flower formation through to seed maturation. They also defend plants against fungal pathogens either alone or in association with chitinases and other antifungal proteins. They are grouped in the PR-2 family of pathogenesis-related (PR) proteins. Use of β-1,3-glucanase genes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
178
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(187 citation statements)
references
References 46 publications
3
178
0
6
Order By: Relevance
“…These enzymes, copious in plants, are involved in several processes during cell division, as the passage of materials through plasmodesmata, and allow plants to tolerate abiotic stresses. β-1,3-glucanase also defends plants against fungal pathogens being able to degrade fungal cell walls either alone or in association with other antifungal proteins (e.g., chitinase isozymes) [41]. …”
Section: Discussionmentioning
confidence: 99%
“…These enzymes, copious in plants, are involved in several processes during cell division, as the passage of materials through plasmodesmata, and allow plants to tolerate abiotic stresses. β-1,3-glucanase also defends plants against fungal pathogens being able to degrade fungal cell walls either alone or in association with other antifungal proteins (e.g., chitinase isozymes) [41]. …”
Section: Discussionmentioning
confidence: 99%
“…The GL153 enzyme is a member of the PR-2 family (Balasubramanian et al 2012), which contributes to plant defenses against fungal infections (Simmons 1994;Kombrink and Somssich 1997), but is also involved in viral pathogenesis (Beffa et al 1996). Iglesias and Meins (2000) reported that a class I b-1,3-glucosidase-silenced line (TAG4.4) showed more resistant to Tobacco mosaic virus infection than wild-type tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of both genes was highly induced after C. fragariae inoculation; however, C. acutatum treatment only induced a slight up-regulation of both genes after 48 h from inoculation (Shi et al 2006). Although plant b-1,3-glucanase genes are generally induced after fungal infection (Balasubramanian et al 2012), this does not seem to be the case for C. acutatum and strawberry interaction. It might be therefore possible that the increased tolerance of bgn13.1 transgenic plants to C. acutatum inoculation would just be due to an increase on total glucanase activity.…”
Section: Discussionmentioning
confidence: 93%